PENGARUH PEMBIAYAAN BAGI HASIL, INFLASI, CURRENT RATIO DAN DEBT TO ASSET RATIO TERHADAP RETURN ON ASSET PADA BANK UMUM SYARIAH YANG TERDAFTAR DI OTORITAS JASA KEUANGAN - Nugroho, Dimas; Riyanti, Riyanti; Hakim, Luqman (Universitas Muhammadiyah Jakarta, 2023)
This research aims to analys determine the effect of profit sharing financing, inflation, current ratio and debt to asset ratio on profitability in this case is a return on asset at Islamic commercial banks at Otoritas Jasa Keuangan with the financial statement period in 2017 - 2021.This study is uses quantitative methods and associative. The data used is secondary data published on the contents of each Islamic banking website. The population in this study are Islamic commercial banks at Otoritas Jasa Keuangan with saturated sample techniques, namely that all populations can be sampled. The data analysis method used in this study was multiple linear regression analysis using version 10 eviews programs.From this study, it explains that the results of profit sharing financing have a significant negative effect on the profitability ratio. in this study, namely return on assets, Inflation has a negative effect on the profitability ratio. in this study, namely return on assets, the current ratio has an insignificant positive effect on profitability ratio in this study, namely return on assets, debt to assets ratio have an insignificant negative on the profitability ratio in this study namely return on assets.